NILAI-NILAI MORAL PADA SYAIR LAGU BERBAHASA JAWA KARYA SUJIWO TEJO - Febriansyah, Iqbal Fauzan; Nurchasanah, Nurchasanah (Hiski Malang, 2023)
Songs can be used to express one's feelings or opinions about something. Sujiwo Tejo's songs, for example, excel in conveying deep and motivating moral principles through meaningful lyrics. Moral value debates are invariably linked to issues of human behavior, and issues of human behavior cannot be isolated from the term